(untitled) (Revista Innova Educación, 2022)
The technological pedagogical content knowledge (TPACK) model is mainly used to measure the integration of new technologies in education. The aim of this study was to analyze the psychometric properties of a version of the TPACK questionnaire for primary school teachers. The methodology is instrumental, the sample consisted of 165 primary school teachers. The instrument used was a scale-type questionnaire composed of 40 items. An exploratory factor analysis, internal consistency, bi-variate, and descriptive correlations were carried out. The results showed that the five-factor model presented the best fit. Positive and statistically significant correlations were found in all dimensions, with technological knowledge and its application in technological pedagogical knowledge, technological content knowledge, and technological pedagogical content knowledge standing out. A high-reliability index (.973) was observed. The results revealed that the primary TPACK questionnaire is a reliable and valid instrument.